Human Eye System Interactive Learning Applications for Elementary School - Lantiunga, Billy Pascal; Rindengan, Yaulie D.Y.; Lumenta, Arie S.M. (Universitas Sam Ratulangi, 2021)
Abstract — The development of Informatics technology in electronic media such as cellphones or mobile phones which have many functions that can facilitate daily human work, commonly called smartphones, which are growing day by day. The use of smartphones for elementary school children is now increasing, because since childhood their parents have accustomed their children to using smartphones with the Android platform. Currently, the applications that are widely circulated are dominated by applications intended for adults, while applications that are useful and specifically intended for elementary schools are still relatively few, and educational materials are still limited. By taking advantage of the many users who use the Android platform today among elementary school children, research is carried out to aim to try to make applications that can make it easier for children to learn about the eye nervous system in humans in this case making interactive learning applications. The research method used is the Multimedia Development Life Cycle (MDLC) which has six stages, namely concept, design, material collecting, assembly, testing and distribution.